Designing a Web-Based Information System for Monitoring Final Projects - Hariyanto, Ferry; Budiman, Thomas; Yulianto, Akmal Budi; Yasin, Verdi (International Journal of Engineering, Science and Information Technology, 2025)
The final project is a crucial requirement for students to complete their studies. At STMIK Jayakarta, the final project monitoring process is still conducted manually using Google Classroom, Google Forms, and WhatsApp. This approach leads to difficulty tracking student progress, data security vulnerabilities, data loss risks, and communication challenges. This study's primary objective is to design a comprehensive web-based monitoring information system that integrates the final project process, from initial registration and guidance to the thesis defence and issuance of the provisional graduation letter. The research design focuses on system modelling, and the Unified Modeling Language (UML) methodology is employed to define system requirements and structure the system's design. The primary outcomes include a detailed system architecture that addresses efficiency, transparency, and accuracy in final project management. The results indicate that this web-based system will significantly improve manual methods, offering better tracking, security, and communication capabilities. In conclusion, this study demonstrates that the proposed system design can serve as a strong foundation for developing a fully functional application, enhancing the effectiveness and transparency of final project management for all stakeholders.